Analysis of the Implementation of SMK3 in the Emergency Assistance for Rehabilitation and Reconstruction (EARR) Project at Mutiara Sis Al Jufri Airport, Palu City - Purwandriono Purwandriono (Pelopor Publikasi Akademika, 2023)
This research was carried out by Purwandriono, number f 11222002 with Supervisor Mrs. Nirmalawati and Mr. Tutang Muchtar Kamaludin, with a background in airports that must continue to operate in line with the implementation of Works Construction, wanting to know the influencing factors, as well as the dominant factors and factors the most dominant in the implementation of the Occupational Safety and Health Management System (SMK3) in the Emergency Assistance for Rehabilitation and Reconstruction (EARR) Project at Mutiara Sis Al Jufri Airport, Palu City. Using the factor analysis method, eight (8) new influential factors were obtained, namely: 1. SOP K3, 2. K3 Reward and Punishment, 3. K3 Work Environment, 4. Role of Management in K3, 5. Role of Workers in K3, 6 .K3 procedures and regulations, 7.K3 implementation, 8.Job safety analysis. This study used a population of 119 staff and project workers and a random sample selection method with the slovin method, a total sample of 55 respondents was obtained. Research data was taken using the questionnaire method, so that the output of data processing was obtained using the factor analysis method, that the factor that had the most significant influence was factor 1 (Standard Operating Procedure/SOP K3), with the variable: The company provided Personal Protective Equipment (PPE) to the employees. project workers. (X11 with a loading factor of 0.895)